(3Sdhc GdeGdc aj JOHQ GdeeGdcs - (3CMeO Hf CHj GdQHjY , TgGH GdOjf CHh GdYHGS CMeO Hf eMeO Hf CHj GdQHjY, GHf CHj GdQHjY,J (B227 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ai CMSf Jbhje hHYO aEf GdPi HYK GdeedRc Ydi JCdja gPG GdcJGH CeQGf GdChd aEfg hba Ydi cJGH ai MaX UMg GdHOf s
(3BNQgG (B:s
(3GdEYJQGa HhLhH GdMb eGfYkG ef JWQb GdZfH abO Je hced HMeO Gddg hYhfg s
(3Cda GdeDda gPG GdcJGH ddeYJUe GdNdjaI GdYHGSi YdjgG ebGHdIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B101s
Keywords: (3GdSjGSI hGdGLJeGYs